The Stereotypical image of science and scientists in the high basic grade students and its relation with some variables in the governorates of Gaza - Al Zaanen, Jamal Abd Rabbuh (Arab Journal for Sciences and Research Publishing, 2015)
The purpose of this study was to assess student's image of science and scientists in high Basic stage students in Gaza Governorate and its relationship with some variables such: sex, grade level and achievement level. The science and scientists image scale was administrated to (231) students who were randomly chosen. Findings obtained from the study revealed that students possess neutral image in general, but they possess negative image about scientists. Results indicated that there are no significant differences in students` image of science and scientists depending on sex and achievement level, but there was significant differences in their image depending on grade level, in favor for higher grade. The study recommended that it is Necessary to negotiate the C.V of the scientists when exposed to their work, during the daily science lessons.
Keywords: Stereotypical image; science and scientists; high basic grade students; achievement level